Occurrence of physical dormancy in seeds of Australian Sapindaceae: A survey of 14 species in nine genera - Cook, A.; Turner, S.; Baskin, J.; Baskin, C.; Steadman, K.; Dixon, Kingsley (Oxford University Press, 2008)
• Background and Aims: Sapindaceae is one of 16 angiosperm families whose seeds have physical dormancy (PY). However, the extent and nature of PY within this family is poorly known. The primary aims of this study were: (1) to evaluate seed characteristics and determine presence (or not) of PY within nine genera of Australian Sapindaceae; and (2) to compare the frequency of PY across the phylogenetic tree within Australian Sapindaceae. • Methods: Viability, imbibition and seed characteristics were assessed for 14 taxa from nine genera of Sapindaceae. For five species of Dodonaea, optimal conditions for germination and dormancy break were evaluated. An in situ burial experiment was performed on D. hackettiana seeds to identify the factor(s) responsible for overcoming PY. Classes of dormancy and of non-dormancy for 26 genera of Sapindaceae were mapped onto a phylogenetic tree for the family. • Key Results: Mean seed viability across all taxa was 69.7 %. Embryos were fully developed and folded (seven genera) or bent (two genera); no endosperm was present. Seeds of all five Dodonaea spp. and of Distichostemon hispidulus had PY. Hot-water treatment released PY in these six species. Optimal germination temperature for seeds of the four Dodonaea spp. that germinated was 15-20°C. Following 5 months burial in soil, 36.4 % of D. hackettiana seeds had lost PY and germinated by the beginning of the winter wet season (May). Laboratory and field data indicate that dormancy was broken by warm, moist temperatures (=50°C) during summer. • Conclusions: PY occurs infrequently in genera of Sapindaceae native to Australia. Seeds of Dodonaea and Distichostemon had PY, whereas those of the other seven genera did not. Seeds of these two genera and of Diplopeltis (a previous study) are the only three of the 20 native Australian genera of Sapindaceae for which germination has been studied that have PY; all three belong to subfamily Dodonaeoideae. © The Author 2008. Published by Oxford University Press on behalf of the Annals of Botany Company. All rights reserved.